1994
DOI: 10.1111/j.1365-2044.1994.tb14190.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and severity of postoperative nausea and vomiting in patients exposed to positive intra‐operative suggestions

Abstract: SummaryIn a double‐blind study, the effects of positive intra‐operative suggestions on the incidence and severity of postoperative nausea and vomiting were studied in 60 patients randomly selected to undergo routine major gynaecological surgery. Patients who received positive suggestions suffered significantly less nausea and vomiting in the 24 h after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…For example, providing positive information has been found to decrease postoperative nausea following gynaecologic surgery [51] and to protect against seasickness in navel cadets [52]. However, as we have argued previously [10] there are two reasons why expectancybased interventions may be more difficult to implement in cancer patients.…”
Section: Discussionmentioning
confidence: 92%
“…For example, providing positive information has been found to decrease postoperative nausea following gynaecologic surgery [51] and to protect against seasickness in navel cadets [52]. However, as we have argued previously [10] there are two reasons why expectancybased interventions may be more difficult to implement in cancer patients.…”
Section: Discussionmentioning
confidence: 92%
“…[23][24][25] Changes in objectively measured outcomes, including reduction in blood loss during surgery 26 and resumption of normal gastrointestinal activity in the postoperative period, 27 have also been observed. A particularly interesting example of how response expectancies affect chemotherapy-related nausea comes from a large multicenter study conducted by our research group examining the efficacy of acustimulation and acupressure bands as an adjunct to standard antiemetics for nausea control.…”
Section: Introductionmentioning
confidence: 98%
“…In our study, only 2 patients required pharmacological therapy for PONV. Previous studies have shown that hypnosis is effective for prevention of nausea and vomiting [1,2,18,19]. All 15 patients in our study also had smooth postoperative course and reported complete amnesia for intra-operative events.…”
Section: Discussionmentioning
confidence: 52%